miR-183 inhibits TGF-β1-induced apoptosis by downregulation of PDCD4 expression in human hepatocellular carcinoma cells - Li, Jipeng (BioMed Central, 2010)
BACKGROUND: In recent years, some miRNAs have been reported to be connected closely with the development of human hepatocellular carcinoma. In our previous studies, a set of miRNAs were revealed to be dysregulated in HCC tissues. However, the functions of these miRNAs in HCC remain largely undefined. METHODS: The expression profiles of miR-183 were compared between HCC tissues and adjacent normal liver tissues using qRT-PCR method. This method was used to screen the potential target genes of miR-183. A luciferase reporter assay was conducted to confirm target association. Finally, the functional effect of miR-183 in hepatoma cells was examined. RESULTS: Among the 25 HCC samples analyzed, microRNA-183 was significantly up-regulated (twofold to 367-fold) in 17 samples compared with the matching nontumoral liver tissues. Programmed cell death 4 (PDCD4) was identified as the target gene of miR-183. Moreover, PDCD4 is a proapoptotic molecule involved in TGF-β1-induced apoptosis in human HCC cells, we found that miR-183 transfectants were resistant to apoptosis induced by TGF-β1. CONCLUSIONS: We conclude that miR-183 can inhibit apoptosis in human HCC cells by repressing the PDCD4 expression, and miR-183 may play an important role in HCC development.